2022
DOI: 10.1371/journal.pone.0262574
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of seven SNP calling pipelines for the next-generation sequencing data of chickens

Abstract: Single nucleotide polymorphisms (SNPs) are widely used in genome-wide association studies and population genetics analyses. Next-generation sequencing (NGS) has become convenient, and many SNP-calling pipelines have been developed for human NGS data. We took advantage of a gap knowledge in selecting the appropriated SNP calling pipeline to handle with high-throughput NGS data. To fill this gap, we studied and compared seven SNP calling pipelines, which include 16GT, genome analysis toolkit (GATK), Bcftools-sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…In addition, different SNP calling tools may report different numbers of SNPs. In a recent comparison using the same dataset at 5-10× sequencing depth (Liu et al, 2022), bcftools, the SNP calling tool used in our study, reported more SNPs than gatk, the SNP calling pipeline used in the Erhualian pigs (Wang et al, 2017) and the Pekin ducks studies (Zhu et al, 2016). Having these considerations, our reported parameters will be an initial reference for future optimization of GBS-based genetic diversity studies on guinea pig populations.…”
mentioning
confidence: 65%
“…In addition, different SNP calling tools may report different numbers of SNPs. In a recent comparison using the same dataset at 5-10× sequencing depth (Liu et al, 2022), bcftools, the SNP calling tool used in our study, reported more SNPs than gatk, the SNP calling pipeline used in the Erhualian pigs (Wang et al, 2017) and the Pekin ducks studies (Zhu et al, 2016). Having these considerations, our reported parameters will be an initial reference for future optimization of GBS-based genetic diversity studies on guinea pig populations.…”
mentioning
confidence: 65%
“…18 Recognized as the industry standard for germline SNV detection, GATK enjoys widespread adoption and has earned a reputation for its reliability and accuracy. 19 Snippy uses a combination of powerful algorithms to analyze genomic data. Leveraging BWA for alignment, Freebayes for variant calling and SnpEff for annotation, Snippy can adeptly identify SNV presence between a haploid reference genome and one or more sequenced samples.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, GATK exhibits proficiency in detecting both SNVs and insertions/deletions, ensuring comprehensive genomic variation analysis 18 . Recognized as the industry standard for germline SNV detection, GATK enjoys widespread adoption and has earned a reputation for its reliability and accuracy 19 . Snippy uses a combination of powerful algorithms to analyze genomic data.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies have shown that the aligner and the variant caller could heavily influence the results of variant detection (O'Rawe et al 2013, Pabinger et al 2014. Additionally, several studies indicated that different tool combinations often generate discordant variant detection results (Cornish et al 2015, Kumaran et al 2019, Liang et al 2019, Liu et al 2022, Wang et al 2019, Zhao et al 2020.…”
Section: Introductionmentioning
confidence: 99%